Absence of associations with prefrontal cortex and cerebellum may link to early language and social deficits in preschool children with ASD - Xin, Jing; Huang, Kaiyu; Yi, Aiwen; Feng, Ziyu; Liu, Heng; Liu, Xiaoqing; Liang, Lili; Huang, Qingshan; Xiao, Yaqiong (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is a complex developmental disorder, characterized by language and social deficits that begin to appear in the first years of life. Research in preschool children with ASD has consistently reported increased global brain volume and abnormal cortical patterns, and the brain structure abnormalities have also been found to be clinically and behaviorally relevant. However, little is known regarding the associations between brain structure abnormalities and early language and social deficits in preschool children with ASD. In this study, we collected MRI data from a cohort of Chinese preschool children with and without ASD (24 ASD/20 non-ASD) aged 12 to 52 months, explored group differences in brain grey matter volume, and examined associations between regional grey matter volume and early language and social abilities in these two groups, separately. We observed significantly greater global grey matter volume in children with ASD as compared to those without ASD, but there were no regional grey matter volume differences between these two groups. For children without ASD, grey matter volume in bilateral prefrontal cortex and cerebellum was significantly correlated with language scores; grey matter volume in bilateral prefrontal cortex was significantly correlated with social scores. No significant correlations were found in children with ASD. Our data demonstrate correlations of regional grey matter volume with early language and social abilities in preschool children without ASD, and the absence of these associations appear to underlie language and social deficits in children with ASD. These findings provide novel evidence for the neuroanatomical basis associated with language and social abilities in preschool children with and without ASD, which promotes a better understanding of early deficits in language and social functions in ASD.